An Interventional Radiologist's Guide to Lung Cancer - Fish, Adam G.; Madoff, David C. (Seminars in Interventional Radiology, 2024)
Lung cancer continues to be the third leading cause of cancer and the leading cause of cancer deaths. As the field of interventional oncology continues to grow, interventional radiologists are increasingly treating lung cancer patients. Involvement begins with tissue diagnosis for which biomarkers and immunohistochemistry are used to guide selective and advanced medical therapies. An interventional radiologist must be aware of the rationale behind tissue diagnosis and techniques to minimize biopsy complications. Staging is an important part of tumor board conversations and drives treatment pathways. Surgical therapy remains the gold standard for early-stage disease but with an aging population the need for less invasive treatments such as radiation therapy and ablation continue to grow. The interventionalist must be aware of the indications, techniques, and pre- and posttherapy managements for percutaneous ablation. Endovascular therapy is broadly divided into therapeutic treatment of lung cancer, which is gaining traction, and treatment of lung cancer complications such as hemoptysis. This review aims to provide a good basis for interventional radiologists treating lung cancer patients.
Keywords: lung cancer; percutaneous ablation; bronchial artery embolization; pulmonary; artery pseudoaneurysms; lung cancer hemoptysis; interventional radiology